2004
DOI: 10.1111/j.1398-9995.2003.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids in colostrum from mothers of children at high risk of atopy in relation to clinical and laboratory signs of allergy in the first year of life

Abstract: The polyunsaturated fatty acid composition of colostrum in a high risk newborn population shows associations with atopic sensitization at the age of 1 year and may be predictive for later atopic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 32 publications
2
43
2
1
Order By: Relevance
“…Furthermore, sCD14 tended to be higher in breast milk received by infants with atopic eczema. There are previous studies on record both supporting and conflicting with our data (25)(26)(27)(28). The immunologic functions of fatty acids in allergy are generally seen to be proinflammatory because n-6 fatty acids may result in increased immunoglobulin E production (6), and against this background, n-3 fatty acid supplementations have been initiated (29,30).…”
Section: Serum and Milk Immunomodulatory Factorscontrasting
confidence: 42%
“…Furthermore, sCD14 tended to be higher in breast milk received by infants with atopic eczema. There are previous studies on record both supporting and conflicting with our data (25)(26)(27)(28). The immunologic functions of fatty acids in allergy are generally seen to be proinflammatory because n-6 fatty acids may result in increased immunoglobulin E production (6), and against this background, n-3 fatty acid supplementations have been initiated (29,30).…”
Section: Serum and Milk Immunomodulatory Factorscontrasting
confidence: 42%
“…However, atopic sensitization occurs early in life; therefore, perinatal n-3 PUFA exposure may affect immune maturation in infants and the risk of subsequent disease. Several studies indicate that the development of allergies may be associated with breast-milk PUFA (8)(9)(10). FO-supplementation of lactating atopic mothers has been found to reduce the prevalence of wheezing in the child (12).…”
Section: Discussionmentioning
confidence: 97%
“…Fish oil (FO) supplementation of pregnant women has been shown to affect immune function in the neonate and atopic sensitization during early life (6,7). Some longitudinal studies found that a higher n-3 PUFA content in breast milk was associated with a decreased likelihood of atopy in infants (8)(9)(10), whereas another study found contrasting results (11). Supplementation with n-3 PUFA during lactation has been found to reduce the prevalence of wheezing during the first 18 mon of life (12).…”
mentioning
confidence: 96%
“…This speculation is based on reports correlating types of fatty acids present in breast milk and the development of asthma and atopy (33)(34)(35). The human breast milk is rich in long-chain polyunsaturated fatty acids, especially -3 (such as eicosapentaenoic acid and docoexaenoic acid) and -6 fatty acids (for example, ␥-linoleic acid and arachidonic acid), which have immunomodulatory actions (36 -38).…”
Section: Discussionmentioning
confidence: 99%